Clinical efficacy of various resuscitation fluids in the management of sepsis in postoperative surgical and trauma patients: a systematic review and meta‑analysis - Yongjie Wang; Kewu Chen; Xiaolu Li; Jianing Guan (Videosurgery and Other Miniinvasive Techniques)
Introduction: Fluid resuscitation is the primary sepsis management strategy aimed at reducing mortality and achieving better treatment outcomes in critically hypotensive patients. Still, there are significant ambiguities regarding the most suitable fluid type that would ensure optimization of patient outcomes.